Application of Functionals in Creating Inequalities. (19th October 2016) - Pavić, Zlatko; Wu, Shanhe; Novoselac, Vedran
Abstract : The paper deals with the fundamental inequalities for convex functions in the bounded closed interval. The main inequality includes convex functions and positive linear functionals extending and refining the functional form of Jensen's inequality. This inequality implies the Jensen, Fejér, and, thus, Hermite-Hadamard inequality, as well as their refinements.